DUKUNGAN PETUGAS KESEHATAN DAN KADER POSYANDU DENGAN UPAYA PENANGANAN DIARE PADA BALITA ( 1– 5 TAHUN ) DI KOTA BANJARMASIN - Edy Ariyanto (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Diarrhea is one of the communicable disease which is cause of death for infants in developing countries. This research aimed to analyse the Support Of Health Workers And Posyandu Cadres with diarrhea  handling feedbacks on the case (1- 5 years) in the working service of health center in banjarmasin in 2015. This study is a quantitative research with cross sectional study design. Total sample 116 respondents. Sampling technique with accidental sampling. Collecting data with interviews using a structured questionnaire that had been tested. Data analysis was performed using univariate, bivariate with chi-square test. The result of this research is no significant correlation between health officer support and posyandu cadres with the effort of handling diarrhea in under fives with p value > 0,05. Suggested for worker and cadres can increase skill and productivity in order to handling diarrhea by trainning and socialization continuously